Textbook of forensic medicine and toxicology - Dikshit, P.C (Peepee Publishers and Distributors (P) Ltd, 2014)
The book covers basic concepts of forensic medicine including medical jurisprudence, forensic pathology, toxicology and forensic sciences in an easy to understand format. All the chapters are concise as well as comprehensive incorporating tables, diagrams, photographs and salient features for a better grasp of the subject. It is a reader-friendly book primarily aimed for undergraduate and postgraduate students and medical officers posted in health care settings and would be beneficial for judiciary and lawyers